Intracellular nanoparticle delivery by oncogenic KRAS-mediated macropinocytosis - Liu X (Dove Medical Press, 2019)
Xinquan Liu, Debadyuti GhoshDivision of Molecular Pharmaceutics and Drug Delivery, College of Pharmacy, The University of Texas at Austin, Austin, TX 78712, USACorrespondence: Debadyuti GhoshCollege of Pharmacy, The University of Texas at Austin, 2409 University Avenue,Austin, TX 78712, USATel +1 512 471 7390Fax +1 512 471 7474Email dghosh@austin.utexas.eduBackground: The RAS family of oncogenes (KRAS, HRAS, NRAS) are the most frequent mutations in cancers and regulate key signaling pathways that drive tumor progression. As a result, drug delivery targeting RAS-driven tumors has been a long-standing challenge in cancer therapy. Mutant RAS activates cancer cells to actively take up nutrients, including glucose, lipids, and albumin, via macropinocytosis to fulfill their energetic requirements to survive and proliferate.Purpose: We exploit macropinocytosis pathway to deliver nanoparticles (NPs) in cancer cells harboring activating KRAS mutations.Methods: NPs were synthesized by the desolvation method. The physicochemical properties and stability of NPs were characterized by dynamic light scattering and transmission electron microscopy. Uptake of fluorescently labelled NPs in wild-type and mutant KRAS cells were quantitively determined by flow cytometry and qualitatively by fluorescent microscopy. NP uptake by KRAS-driven macropinocytosis was confirmed by pharmacological inhibition and genetic knockdown.&#x00A0Results: We have synthesized stable albumin NPs that demonstrate significantly greater uptake in cancer cells with activating mutations of KRAS than monomeric albumin (ie, dissociated form of clinically used nab-paclitaxel). From pharmacological inhibition and semi-quantitative fluorescent microscopy studies, these NPs exhibit significantly increased uptake in mutant KRAS cancer cells than wild-type KRAS cells by macropinocytosis.Conclusions: The uptake of albumin nanoparticles is driven by KRAS. This NP-based strategy targeting RAS-driven macropinocytosis is a facile approach toward improved delivery into KRAS-driven cancers.Keywords: albumin nanoparticles, KRAS mutation, macropinocytosis